Strategi Guru PAI Dalam Meningkatkan Membaca Al-Qur’an Siswa Kelas 6 Di MIS Nurul Ikhwan - Siregar, Pani Akhiruddin; Zuhri, Mutiara; Nulhaq, Aulia Rohmah (Journal of Sustainable Education, 2025)
Learning to read the Qur'an is one of the main components of Islamic religious education that must be possessed by students, especially at the Madrasah Ibtidaiyah level. This study aims to assess the strategies implemented by Islamic Religious Education (PAI) teachers in developing the ability to read the Qur'an of grade 6 students at MIS Nurul Ikhwan. The method applied in this study is qualitative with data collection through observation, interviews, and documentation. Research indications suggest that PAI teachers implement several successful strategies, including effective learning planning, application of the listening and practicing method, use of interactive learning media, and providing motivation and working together with parents. Several supporting factors are teacher ability, adequate facilities, and adequate learning environment, while the inhibiting factors are lack of student motivation and limited attention from parents. With this, it can be concluded that the strategies implemented by PAI teachers have an important role in improving the ability to read the Qur'an of grade 6 students at MIS Nurul Ikhwan.